101 Great Answers To The Toughest Interview Questions - Ron Fry
For years, interviewees have relied on 101 Great Answers to the Toughest Interview Questions. In fact, more than 500,000 people have used prior editions. The book begins with an overview of the interviewing process. Then, questions are grouped by chapter to cover the full range of possible interview topics--everything from, "Why are you thinking of leaving your current job?" to "When can you start?" This brand new edition is thoroughly updated to reflect the realities of today's job market.